Changes in the Autonomic Nervous System in Patients Poisoned by Cauterizing Liquids - T. G. Fedorenko; A. A. Lavrentyev; G. N. Sukhodolova; A. V. Badalyan (Общая реаниматология, 2007)
Objective: to examine changes in the function of the autonomic nervous system (ANS) in patients with intoxication with cauterizing liquids in relation to the condition of patients in order to early determine the prognosis of the disease. Subjects and methods. ANS was studied in 130 patients aged 15 to 82 years who had been poisoned by cauterants, treated at the Toxicological Unit, Voronezh Regional Hospital, and at the Center for Acute Intoxication Treatment, N. V. Sklifosovsky Research Institute of Emergency Care, Moscow, in 2004—2006. Cardiointervalographic parameters were analyzed in relation to the condition of patients, the time elapsed after intoxication prior to the patients’ admission to a specialized hospital, the presence of hemolysis and blood alcohol, the degree of upper gastrointestinal mucosal burn, and the pattern of poisoning (accidental or intentional). Results. Within the first hours after intoxication with cauterizing liquids, ANS was found to be impaired, which was associated with the development of hyper-sympathicotonia caused by the increased activity of its sympathetic part and the decreased tone of the parasympa-thetic one. The magnitude of hypersympathicotonia depends on the severity of poisoning, on the time elapsed after the onset of intoxication, on the presence of hemolysis, the blood content of alcohol, the degree of upper gastrointestinal burn, and the nature of poisoning. The preponderance of the tone of the ANS parasympathetic part suggests the disturbance of adaptive and compensatory mechanisms and a poor prognosis. Conclusion. Cardiointervalography is recommended for the objective evaluation of the severity of poisoning with cauterizing liquids and the efficiency of performed therapy and for the prediction of the outcome of the disease. Key words: cauterizing liquids, autonomic nervous system, cardiointervalography, adaptive and compensatory mechanisms.